Interkulturelle Zusammenarbeit in multinationalen Teams - Cramer, Tobias (2007)
The overall goal of the dissertation is to understand cross-cultural cooperation in multinational teams and to find ways to help improve such ciiperation.For this, the study of matters was theoretically analysed first,secondly a model of influencing factors for successful multicultural teams was presented, and finally ,the derived hypotheses were tested in a field study.